2017
DOI: 10.1021/acs.macromol.7b01217
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chain Rigidity on the Decoupling of Ion Motion from Segmental Relaxation in Polymerized Ionic Liquids: Ambient and Elevated Pressure Studies

Abstract: Conductivity in polymer electrolytes has been generally discussed with the assumption that the segmental motions control charge transport. However, much less attention has been paid to the mechanism of ion conductivity where the motions of ions are less dependent (decoupled) on segmental dynamics. This phenomenon is observed in ionic materials as they approach their glass transition temperature and becomes essential for design and development of highly conducting solid polymer electrolytes. In this paper, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
87
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 65 publications
5
87
0
Order By: Relevance
“…S6, Supporting Information). We attributed the remaining conductivity difference after normalization of mobility to the additional effects such as decoupling of segmental dynamics from the counter‐ion dynamics . This trend agrees well with PILs in which ionic groups are separated from the polymer backbone .…”
Section: Resultssupporting
confidence: 80%
“…S6, Supporting Information). We attributed the remaining conductivity difference after normalization of mobility to the additional effects such as decoupling of segmental dynamics from the counter‐ion dynamics . This trend agrees well with PILs in which ionic groups are separated from the polymer backbone .…”
Section: Resultssupporting
confidence: 80%
“…Figure 4 demonstrates density versus temperature relation of both HPs and di-BCPs with varying charge ratio. Glass transition temperature (Tg) can be obtained by the change in the thermal expansion coefficient [32,33,34]. Tg of both charged HPs and BCPs gradually increase with charge ratio.…”
Section: Resultsmentioning
confidence: 99%
“…91 Correlating the degree of decoupling with the flexibility (i.e., the fragility) of the poly(IL) electrolyte by comparing the relatively rigid vinyl-based poly(IL)s and the rather flexible siloxanetype poly(IL)s, confirmed that there is a direct relationship between the chain packing frustration (due to the polymer fragility) and the decoupled ionic motion within the resulting free volume. 92 As a matter of fact, the authors observed a decreased decoupling under elevated pressure, especially for rather flexible poly(IL)s. For rigid poly(IL) electrolyte, however, this effect was less pronounced, highlighting the importance of the free volume.…”
Section: B) Frustrated Polymers and Polymerized Ionic Liquidsmentioning
confidence: 98%